ANALISIS KINERJA DINAS KEBERSIHAN DAN PERTAMANAN KOTA SEMARANG DALAM MEWUJUDKAN SANITASI PERKOTAAN PADA SEKTOR PERSAMPAHAN - Abdurrahman, Ananda Rifqi; Yuniningsih, Tri; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Health is a main priority is the human that which is not separated relation to sanitation.Of the four sanitation sector where among other clean water waste, waste, and drainage, in this research focused on the waste which are managed and it is determined by the performance of semarang city department of hygiene and urban landscapping.The problems underlying this research is waste semarang city as a problem of waste management and less orptimal the performance of semarang city department of hygiene and urban landscapping.This research is written with a method of descriptive qualitative.The purpose of this research is described and analyzing the performance of semarang city department of hygiene and urban landscapping using indicators the quality of services for the society responsiveness, responsibilitas, and accountability.The selection of informants technique with snowball technique and the keyperson is head of planning and evaluation. The result of this research in terms of service quality indicators , responsiveness , in the level of effectiveness and accountability still being awake , but on the responsibility still have obstacles and gave rise to the barrier is a factor of human resources of factor and hygiene facilities and infrastructure and parks department already have a solution that has been applied namely cooperation with third parties and a solution that will be done is the withdrawal of investors in waste management . Based on the results of research that can conclude in a city park agency and less optmal semarang.Therefore, it was the advice given and recruitment in a special team of technical experts in the field, a deep understanding exercise and technical knowledge about the environment and waste to the employee performance to solve the problem, as well as facilities and infrastructure especially by heavy equipment belongs to semarang city department of hygiene and urban landscapping could be more optimal.